Entrepreneurial Narratives and Entrepreneurial Intention Among Undergraduate University Students in Kenya - Kosgei, Chenuos N.; Michael, Korir; Ernest, Saina (African Journal of Education,Science and Technology (AJEST), 2021)
In the establishment of new businesses, individual entrepreneurial intent is a crucial component. In entrepreneurship theory and research, entrepreneurial intention has shown to be a critical and continuous phenomenon. Despite vocational training institutes teaching youths with the goal of going into self-employment, a substantial percentage of them continue to look for paid work, with many of them being unemployed with poor entrepreneurial aspirations. Yet, the entrepreneurial narratives are critical to understanding the process of entrepreneurship in relation to growth of the firms. The relationship between entrepreneurial intentions and entrepreneurial narrative of established small firms are neglected. Thus, the broad objective was to investigate the effect of entrepreneurial narratives (knowledge, inspiration and transportation) on entrepreneurial intentions. The study had a positivist perspective and used an explanatory research approach. Between January and May 2019, the population comprised of undergraduate university students in their fourth year of study who were enrolled in business-related courses. Techniques such as proportionate, stratified, and random sampling were used. A total of 400 students were chosen from universities in Nyanza and Western Kenya for the study. Structured questionnaires with likert interval measures were used to obtain primary data. The hypothesis was tested using Hayes model six. The findings of the study revealed that knowledge had a favorable impact on entrepreneurial intent (β=0.47, p<.05), inspiration (β=0.14, p<.05) and transportation (β=0.14, p<.05) were significantly associated with entrepreneurial intention. The findings conclude that entrepreneurial narratives encourage entrepreneurial intention among university students. Further, students which deduce knowledge, inspiration transportation from entrepreneurial narratives exhibit high entrepreneurial intention as results of human behavior. As a result, the study recommends that students’ attitude toward conduct and perceived behavioral control be improved in order to boost entrepreneurial intent. For example, students may be persuaded that starting their own business is a better alternative for their career and that they can control the process of starting a new company.